SPIRITUAL VALUES IN BIOLOGICAL MATERIALS: PLANTS GROWTH AND DEVELOPMENT - lutfauziah, asmaul; Handriyan, Aris (http://jagadalimussirry.com/, 2018)
Spiritual value is a value that reflects human relations with their God. The spiritual value contained in each Biology material is different. This value can be taught well when the teacher has understood the spiritual value contained in the subject being taught. The subject of